Analisis Kemampuan Berpikir Kritis Matematis Peserta Didik Kelas VIII SMP Negeri 3 Payakumbuh Menggunakan Watson-Glaser Critical Thinking Appraisal - ANGGUN DWISA INDAH (Jurnal Edukasi dan Penelitian Matematika, 2019)
One of the abilities that must be developed in mathematics learning is the ability to think critically. But in learning and assessment the results of mathematics learning the ability to think critically is not a concern. There is a test that is widely used to measure students' critical thinking skills, namely Watson-Glaser Critical Thinking Appraisal (WGCTA). The research objective is to describe the level of students' critical thinking skills based on the WGCTA indicator. This type of research is descriptive research with a qualitative approach. The research subjects were students of class VIII-1 who were selected based on certain considerations. The research instrument is in the form of test questions and interview guidelines. The data obtained are the results of tests regarding critical thinking skills and the results of interviews. The analysis techniques used include data reduction, data presentation and conclusion drawing. The guarantor technique for the validity of the data used is technical triangulation. Based on the results of analysis and triangulation, it can be concluded that students' critical thinking skills are in the moderate category. The level of critical thinking skills of students is classified as being on the indicator of deduction and interpreting information, classified as low to moderate on indicators of inference and analysis of arguments, classified as low on the indicator of assumption (regnition of recommendations) . Keywords - analysis, critical thinking skills, Watson-Glaser Critical Thinking Appraisal